Management of Intrathoracic Benign Schwannomas of the Brachial Plexus. (22nd July 2014) - Bandiera, Alessandro; Negri, Giampiero; Melloni, Giulio; Mandelli, Carlo; Gerevini, Simonetta; Carretta, Angelo; Ciriaco, Paola; Puglisi, Armando; Zannini, Piero
Abstract : Primary tumours of the brachial plexus are rare entities. They usually present as extrathoracic masses located in the supraclavicular region. This report describes two cases of benign schwannomas arising from the brachial plexus with an intrathoracic growth. In the first case the tumour was completely intrathoracic and it was hardly removed through a standard posterolateral thoracotomy. In the second case the tumour presented as a cervicomediastinal lesion and it was resected through a one-stage combined supraclavicular incision followed by left video-assisted thoracoscopic surgery. A brachial plexus tumour should be suspected not only in patients with a supraclavicular or cervicomediastinal mass but also in those with intrathoracic apical lesions. A preoperative magnetic resonance imaging study of brachial plexus should be performed in such cases in order to plan the correct surgical approach.